Program Campus Social Responsibility (CSR) ONE TO ONE UM Surabaya sebagai Upaya Menekan Angka Anak Putus Sekolah di Kota Surabaya - Rahayu, Aristiana Prihatining; Poerwanto, Agoes; Ngatmain, Ngatmain (Aksiologiya: Jurnal Pengabdian Kepada Masyarakat, 2021)
Pesatnya jumlah dan sebaran permasalahan sosial kota Surabaya, belum sebanding dengan daya jangkau, kapasitas, dan, kemampuan pelayanan sosial yang dilakukan pemerintah. Kewajiban pemerintah dalam memenuhi hak-hak dasar warganya belum dapat terlaksanakan secara maksimal, termasuk dalam persoalan pendidikan. Untuk itu, pemerintah kota Surabaya melalui Dinas Sosial bekerja sama dengan perguruan tinggi negeri dan swasta yang ada di kota Surabaya untuk memberikan pendampingan pendidikan kepada anak dari keluarga penyandang masalah kesejahteraan sosial (miskin), yang rentan atau putus sekolah melalui program Campus Social Responsibility (CSR) One to One.  Dalam proses pelaksanaannya, mahasiswa diterjunkan untuk melakukan berbagai program pendampingan yang mengarah pada tujuan besar yakni menekan angka anak rawan dan putus sekolah. Sasaran dari program adalah anak dari keluarga penyandang masalah kesejahteraan sosial (PMKS) yang putus atau rentan putus sekolah, yang terdata Dinas Sosial Kota Surabaya.  Luarannya adalah  terbangunnya motivasi adik damping untuk tetap semangat sekolah, dan mengembalikan mereka yang putus sekolah untuk kembali ke bangku sekolah. Metode pelaksanaannya_ koordinasi antara dinas sosial dan PTN/PTS di Kota Surabaya , sosialisasi program ke mahasiswa, perekrutan tim CSR, pelaksanaan pendampingan dan evaluasi. Indikator program CSR ini adalah mahasiswa mampu mengembalikan adik damping mereka yang rentan maupun putus sekolah, untuk kembali dan makin termotivasi bersekolah.  kata kunci : campus social responsibility , dinas sosial, mahasiswa  One To One UM Surabaya Campus Social Responsibility (CSR) Program as an Effort to Reduce the Number of Children Dropping Out of School in the City of SurabayaABSTRACTThe rapid number and distribution of social problems in the city of Surabaya is not yet comparable to the reach, capacity and ability of social services provided by the government. The government's obligation to fulfill the basic rights of its citizens has not been maximally implemented, including in matters of education. For this reason, the Surabaya city government through the Social Service collaborates with public and private universities in the city of Surabaya to provide educational assistance to children from families with social welfare problems (poor), who are vulnerable or drop out of school through the One to One Campus Social Responsibility (CSR) program. In the implementation process, students are deployed to carry out various mentoring programs that aim at the big goal of reducing the number of vulnerable children and dropping out of school. The target of the program is children from families with social welfare problems (PMKS) who drop out or are prone to dropping out of school, which is recorded by the Surabaya City Social Service. The result is the awakening of the motivation of the assistants to keep up the spirit of school, and to return those who drop out of school to return to school. The method of implementation is coordination between social services and PTN / PTS in the city of Surabaya, socialization of the program to students, recruitment of CSR teams, implementation of mentoring and evaluation. The indicator of this CSR program is that students are able to return their siblings who are vulnerable or drop out of school, to return and be more motivated to go to school.keywords: campus social responsibility, social service, student